Funding and services needed to achieve universal health coverage: applications of global, regional, and national estimates of utilisation of outpatient visits and inpatient admissions from 1990 to 2016, and unit costs from 1995 to 2016. (January 2019) - Moses, Mark W; Pedroza, Paola; Baral, Ranju; Bloom, Sabina; Brown, Jonathan; Chapin, Abby; Compton, Kelly; Eldrenkamp, Erika; Fullman, Nancy; Mumford, John Everett; Nandakumar, Vishnu; Rosettie, Katherine; et al.
Summary: Background: To inform plans to achieve universal health coverage (UHC), we estimated utilisation and unit cost of outpatient visits and inpatient admissions, did a decomposition analysis of utilisation, and estimated additional services and funds needed to meet a UHC standard for utilisation. Methods: We collated 1175 country-years of outpatient data on utilisation from 130 countries and 2068 country-years of inpatient data from 128 countries. We did meta-regression analyses of annual visits and admissions per capita by sex, age, location, and year with DisMod-MR, a Bayesian meta-regression tool. We decomposed changes in total number of services from 1990 to 2016. We used data from 795 National Health Accounts to estimate shares of outpatient and inpatient services in total health expenditure by location and year and estimated unit costs as expenditure divided by utilisation. We identified standards of utilisation per disability-adjusted life-year and estimated additional services and funds needed. Findings: In 2016, the global age-standardised outpatient utilisation rate was 5·42 visits (95% uncertainty interval [UI] 4·88–5·99) per capita and the inpatient utilisation rate was 0·10 admissions (0·09–0·11) per capita. Globally, 39·35 billion (95% UI 35·38–43·58) visits and 0·71 billion (0·65–0·77) admissions were provided in 2016. Of the 58·65% increase in visits since 1990, population growth accounted for 42·95%, population ageing for 8·09%, and higher utilisation rates for 7·63%; results for the 67·96% increase in admissions were 44·33% from population growth, 9·99% from population ageing, and 13·55% from increases in utilisation rates. 2016 unit cost estimates (in 2017 international dollars [I]) ranged from I2 to I478 for visits and from I87 to I22 543 for admissions. The annual cost of 8·20 billion (6·24–9·95) additional visits and 0·28 billion (0·25–0·30) admissions in low-income and lower-middle income countries in 2016 was I503·12 billion (404·35–605·98) or US158·10 billion (126·58–189·67). Interpretation: UHC plans can be based on utilisation and unit costs of current health systems and guided by standards of utilisation of outpatient visits and inpatient admissions that achieve the highest coverage of personal health services at the lowest cost. Funding: Bill & Melinda Gates Foundation.